New representation for the 2-to-4 gluon vertex in high energy QCD - Ewerz, Carlo (Physics letters, 2000)
A new representation for the two-to-four gluon vertex arising in the context of unitarity corrections is derived which involves only BFKL kernels. We discuss possible implications of this representation, including the possibility of finding the NLO corrections to the vertex.